Potamolinea gen. nov. (Oscillatoriales, Cyanobacteria): A phylogenetically and ecologically coherent cyanobacterial genus - Martins, Mariéllen Dornelles [UNESP]; Branco, Luis Henrique Zanini [UNESP] (Microbiology Society, 2016)
Phormidium Kützing ex Gomont, a common genus of the Cyanobacteria, is widely known as a problematic group. Its simple morphology is not congruent with its genetic heterogeneity and several new generic entities have been described based on 16S rRNA gene sequence analyses from populations with similar morphology. During a study of the diversity of Phormidioideae (Phormidiaceae, Oscillatoriales) in Brazil, ten Phormidium-like strains from south-eastern and mid-western regions were isolated in monospecific cultures and submitted to polyphasic evaluation (morphological, ecological and molecular studies). The populations studied presented homogeneous morphology (trichomes straight, not attenuated and apical cell rounded or obtuse), differing mainly in cell length from the type species of the genus Phormidium (Phormidium lucidum Agardh ex Gomont) and occurring as three morphotypes. Phylogenetic analysis based on 16S rRNA gene sequences revealed that the populations studied, with European Phormidium aerugineo-caeruleum (Gomont) Anagnostidis & Komárek strains, were placed together in a very distinctive and highly supported clade. Thus, the set of characteristics of the strains resulted in the recognition of the new genus Potamolinea Martins et Branco with two species: Potamolinea magna as the type species (strains 47PC and 48PC) and Potamolinea aerugineo-caerulea (Gomont) Martins et Branco (strains 1PC, 2PC and 38PC). These two species plus one still undetermined lineage, Potamolinea sp., are morphologically and genetically distinguishable, whereas the secondary structures of the D1-D1′, box-B and V3 regions were conserved within each one. The generic name and specific epithets of the new taxa are proposed under the provisions of the International Code of Nomenclature for algae, fungi and plants.
Keywords: 16S rRNA; 16S-23S ITS; Brazil; Morphological evaluation; Phylogenetic analysis; Taxonomy